Discovery of the large-scale thrust nappe and its geological significance in the southwestern Santanghu fold–thrust belt, NW China - Zhen, Yu; Xu, Xiongfei; He, Dengfa; Li, Xinning; Li, Di (Frontiers in Earth Science, 2023)
Studying the structural evolution of the piedmont fold and thrust belt is one of the most important methods to interpret the mechanism of intracontinental collision orogeny. In this study, we have discovered a long-distance large-scale thrust nappe with a width of approximately 20 km in the southwestern margin of the Santanghu Basin, which provides a good evidence for studying the Mesozoic–Cenozoic tectonic evolution mechanism of Moqinwula Mountain. Using the electromagnetic and high-resolution seismic profiles, we have determined that the hanging wall of the nappe is composed of the pre-growth strata of the Carboniferous–Middle Jurassic period and the syntectonic strata of the Cretaceous–Quaternary period. The nappe is subjected to two branch faults of the Baiyishan thrust, forming a breakthrough fault-propagation fold and a fault-bend fold along the detachment layer of the Haerjiawu Formation, and a large monoclinic is formed by the basement structural wedge near the mountain root. The growth strata and unconformity structure record that the fold–thrust belt has experienced five episodes of thrusting from the Late Triassic to Quaternary period. Based on sequential restoration and forward modeling, we propose that the southwestern margin of the Santanghu Basin has been shortened by at least 55 km, especially in the Late Jurassic and Late Cretaceous. Our results provide an excellent example for studying the mechanism of the transition from Yanshanian transpression to Himalayan thrust compression in the Eastern Tianshan region.